Man's physical world - Van Riper, Joseph E. (McGraw-Hill, 1971)
Abler recalls the use of the textbook Man's Physical World by J. E. Van Riper in his introductory physical geography course at Penn State's College of Education. While he was pleased with the textbook, it missed connecting with the background and motivation of his students.